Improving The Effectiveness of Primary School Administration Services Based on The Education Management Information System With The Dapodik Application And Education Service Facilities - Udiyana, Ida Bagus Gede; Putri, Anak Agung Made Anggita Yuliari; Utari, Ida Ayu Putu Ari; Astini, Ni Nyoman Seri; Kusuma, I Nyoman Ari; Karwini, Ni Ketut (Journal of Management Economic and Financial, 2023)
The purpose of this research is to determine and analyze the use of the Dapodik application and educational service facilities on the effectiveness of administrative services and to analyze the factors for the success of using the Dapodik application and the quality of educational services on the effectiveness of administrative services at SD Saraswati 1 Denpasar, Bali - Indonesia. The results of the research show that the weaknesses of using the Dapodik application-based education management information system are that some students are still not punctual in completing administrative documents, the limited number of operators in operating the application and processing data, the consistency of the application of the Dapodik application system often changes causing school operators to have to re-input in each school year. Factors that influence the effectiveness of the use and implementation of the Dapodik application (1) support from a good information system, (2) support from an excellent internet network, (3) participation and coordination of school principals, teachers and parents, (4) administrative staff educational services are competent, professional, responsible and able to coordinate well. (5) Facilities and infrastructure are good and of good quality.